THE URGENCY OF CADRE EDUCATION SYSTEM AT DARUNNAJAH CIPINING ISLAMIC BOARDING SCHOOL - Amin Songgirin (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2020)
The orientation of Darunnajah Cipining Islamic Boarding School cadre program is to give birth to the best/selected human group, becoming a core force or backbone to defend, support and advance the Darunnajah Cipining Islamic Boarding School called Asḥāb al-Najāh. The results of the regeneration process are cadres who have integrity, loyalty, are dedicated, moveable, capable, reliable and militant to realize the ideals of the pesantren and maintain the sustainability of the institution until the Day of Judgment. In the cadre system research at Darunnajah Cipining Islamic Boarding School, using a qualitative approach based on the philosophy of phenomenology, through deep appreciation. The qualitative method tries to understand and interpret the meaning of an event of human behavior interaction in a particular situation according to the researcher’s perspective. This approach is directed at the background and the whole individual and does not isolate individuals or institutions into variables or hypotheses, but sees it as part of a whole. The results of this study are the cadre education system at Darunnajah Cipining Islamic Boarding School, which since its establishment has implemented a 16-year compulsory education for cadres, and forges its cadres through education, both formal and direct life practice activities, through training and assignments. Cadre formation in Darunnajah Cipining Islamic Boarding School as a cycle that continues to spin with gradations with several stages. Cadre education is an investment in knowledge, skills and attitudes towards students